The Effects of Metals and Ocean Acidification on Marine Invertebrates - Siddiqui, Samreen (2015)
Increasing use of metal oxide nanoparticles (NP) by various industries has resulted in substantial contributions of NP in aquatic systems. Additionally, ocean acidification (OA) is a growing concern due to its deleterious effects on aquatic organisms. The effects of OA and metal pollution on non-calcifying marine organisms are largely unknown. This research investigated the effects of copper oxide (CuO) NP on the sea anemone, Exaiptasia pallida, for 21 days. Sea anemones were measured for tissue copper accumulation as well as the activity of the enzymes: catalase (CAT), glutathione peroxidase (GPx), glutathione reductase (GR), and carbonic anhydrase (CA). This study is useful in discerning the differences between CuO NP and dissolved copper exposure to sea anemones, as differences in copper accumulation pattern and enzymatic response were observed. In addition, we examined physiological effects of the sea anemone, Exaiptasia pallida after exposure to a global stressor, CO2, and a local stressor, Cu, over 7 days. Cu accumulated in E. pallida in a concentration-dependent manner and activities of all anti-oxidant enzymes measured (CAT, GPx, GR) increased, with increasing Cu exposure. However, clear differences in only GR and to some degree GPx activity were observed due to increasing CO2 exposure alone. Interactions between the two independent variables were also observed. Activity of the enzyme, CA, was significantly decreased with increasing Cu and the extent of CA inhibition was lessened with increasing CO2. These results provide insight into toxic mechanisms of CuCl2, CuO NP and CO2 exposure to E. pallida. I. COMPARATIVE EFFECTS OF DISSOLVED COPPER AND COPPER OXIDE NANOPARTICLE EXPOSURE TO THE SEA ANEMONE, EXAIPTASIA PALLIDA Introduction - 1 | Material and Methods - 3 | Results - 7 | Discussion and Conclusion - 11 | II. RESPONSES OF THE SEA ANEMONE, EXAIPTASIA PALLIDA, TO OCEAN ACIDIFICATION CONDITIONS AND COPPER EXPOSURE Introduction - 21 | Material and Methods - 23 | Results - 27 | Discussion and Conclusion ...